McGraw-Hill dictionary of earth science - Parker, Sybil P (McGraw-Hill, 1997)
Including more than 8500 definitions in the earth sciences, this comprehensive dictionary offers a complete and handy source for terminology used in the fields of climatology; geochemistry; geodesy; geography; geophysics; hydrology; mapping; meterology; oceanography; and palaeontology.